Violencia familiar en el pueblo de Madrid durante el siglo XVIII - Ortega López, Margarita (Cuadernos de Historia Moderna, 2006)
The principal purpose of this study is to identify some of the causes that gave rise to violence within lower –class families in eighteenth– century Madrid. Emphasis is placed on the conditions leading to marriage as well as the usual reasons for conflicts within married couples, especially in the second half of the century. The principal sources used derive from the Madrid criminal court (Sala de Alcaldes) in the National Archive.